2007
DOI: 10.1002/ange.200700113
|View full text |Cite
|
Sign up to set email alerts
|

Carbanionen mit zwei N‐Substituenten als nucleophile Acyltransfer‐Reagentien

Abstract: Professor Helge Willner zum 60. Geburtstag gewidmet Unter den vielen verschiedenen carbanionischen Systemen nehmen solche, in denen das Carbanion an ein N-Atom gebunden ist, eine besondere Stellung ein, weil sie zu der Gruppe formal nicht-oder destabilisierter Carbanionen gehören.[1] Dies wird verständlich, wenn man die Abstoßung zwischen dem Carbanion und dem freien Elektronenpaar am N-Atom berücksichtigt. Aus diesem Grund sind a-lithiierte Amine generell nur schwierig direkt durch Deprotonierung aus den ents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 38 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…All the anticipated different types of hydrogen atom in 2 are accounted for and well resolved in Similarly the 13 C NMR spectrum of 2 is easily fully assignable (see Supporting Information for details). The molecular structure of 2 ( Figure 1) [9] is mononuclear, with both Zn and N(Me') atoms chiral as each is attached to four different substituents, though overall the crystal structure is centrosymmetric and hence the material is racemic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All the anticipated different types of hydrogen atom in 2 are accounted for and well resolved in Similarly the 13 C NMR spectrum of 2 is easily fully assignable (see Supporting Information for details). The molecular structure of 2 ( Figure 1) [9] is mononuclear, with both Zn and N(Me') atoms chiral as each is attached to four different substituents, though overall the crystal structure is centrosymmetric and hence the material is racemic.…”
mentioning
confidence: 99%
“…In the final step, one tBu ligand deprotonates one NMe 2 arm of TMEDA to build an N-CH 2 -Zn bridge, while concomitantly reduced steric constraints around the Zn center allow the free Me 2 N terminal of the benzene-tethered TMEDA to datively bind to Zn to close a seven-atom (ZnCCNCCN) ring. Usually a-metalations of amines [13] have high kinetic barriers and would conventionally be considered impossible for only mildly electropositive zinc, but here the barrier must be reduced substantially by the close proximity of the tethered tBu 2 Zn and TMEDA units which sets up a favorable intramolecular Zn-H exchange reaction with loss of BuH. [14] As aforementioned, loss of the halogen substituent distinguishes this new alkali metal mediated zincation (AMMZn) reaction from those of "LiZn(TMP)(tBu) 2 ", which, when intercepted by electrophiles, give polysubstitut- Communications ed haloarenes.…”
mentioning
confidence: 99%
“…Thereby, the bulky alkyl moieties prevent precoordination according to the CIPE concept, which at the analogous methyl-substituted compound TMTAC brings BuLi in proximity to a proton and initiates the deprotonation. [5][6][7]…”
Section: Resultsmentioning
confidence: 99%
“…[5] A few years ago, we reported that the reaction of 1,3,5-trimethyl-1,3,5triazacyclohexane (TMTAC) with butyllithium resulted in selective deprotonation of a methylene group (Scheme 1). [6] The resulting N 2 CHLi substitution-type carbanion proved to be applicable as a reagent for Corey-Seebach-type formyl group transfer. The initially unexpected selectivity of metalation found explanation in terms of the complex-induced proximity effect (CIPE), [7] after Strohmann et al isolated a precoordination complex of TMTAC with a trimeric tBuLi fragment.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Such base-induced formation of methyllanthanide cations was also observed upon the action of crown ethers to Ln(AlMe 4 ) 3 reagents (Ln = Y, Pr). [20] The many reaction types and the formation of mixtures make it desirable to understand the factors for selectivity and to find conditions under which certain species can be prepared exclusively and in high yield. In this contribution we show that selectivity for the formation of the aluminate dianions [ 3-can be steered by the correct choice of ligand size (R) and the appropriate metal ion (Ln).…”
Section: Introductionmentioning
confidence: 99%